Livestock markets and resilient drylands - Shikuku, Kelvin Mashisia (International Livestock Research Institute, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025